Examining the Influence of Push and Pull Travel Motivation Factors on Domestic Tourism Performance. A Case of Mombasa County, Kenya - Mshai, Mwawaza Stella; Kariuki, Albert C; Ndubi, Edgar O (My University, 2022)
Understanding tourist’s motivations to visit destinations is important as it helps in segmenting the markets thereby allowing tourism stakeholders to correctly target them. This study aimed at establishing the influence of push and pull travel motivation factors on domestic tourism performance in Mombasa County, Kenya. The study used cross-sectional descriptive research to collect data from a sample of 400 domestic tourists. The data was gathered through a well-structured questionnaire administered randomly. The data was analysed using descriptive and inferential statistics. The findings indicated a significant influence of pull factors (p=0.000≤0.05) and push factors (p=0.000≤0.05) on domestic tourism performance. The pull factors identified include beautiful natural attractions, other diverse attractions, culture of the area, image, ease of access, events taking place, affordability, safety and security and recommendations by others while the important push factors included prestige, knowledge, adventure and novelty, and relaxation and health. The results further revealed that the pull factors had more influence on domestic tourism performance than the push factors. These findings could benefit the stakeholders in identifying the internal motives of their potential clients, which could help match the clients’ desires with what the destination has to offer. The study recommended that stakeholders are required to package tourism products in line with tourists’ motivation failure to which the product may not be purchased. Therefore, there is need to ensure that the destination has diverse beautiful and cultural attractions, diverse events and activities, is affordable, safe, easily accessible, and has a positive image necessary to attract domestic tourists.
Keywords: Push factors; pull factors; motivation; domestic tourists; domestic tourism performance; Mombasa